Contribution of BRCA1 and BRCA2 Germline Mutations to Early Algerian Breast Cancer. (22nd February 2016) - Henouda, Sarra; Bensalem, Assia; Reggad, Rym; Serrar, Nedda; Rouabah, Leila; Pujol, Pascal
Abstract : Breast cancer is the most common female malignancy and the leading cancer mortality cause among Algerian women. Germline mutations in the BRCA1 and BRCA2 genes in patients with early-onset breast cancer have not been clearly identified within the Algerian population. It is necessary to study the BRCA1/2 genes involvement in the Algerian breast cancer occurrence. We performed this study to define germline mutations in BRCA1/2 and their implication in breast cancer among young women from eastern Algeria diagnosed or treated with primary invasive breast cancer at the age of 40 or less who were referred to Anti-Cancer Center of Setif, Algeria. Case series were unselected for family history. Eight distinct pathogenic mutations were identified in eight unrelated families. Three deleterious mutations and one large genomic rearrangement involving deletion of exon 2 were found in BRCA1 gene. In addition, four mutations within the BRCA2 gene and one large genomic rearrangement were identified. Novel mutation was found among Algerian population. Moreover, five variants of uncertain clinical significance and favor polymorphisms were identified. Our data suggest that BRCA1/2 mutations are responsible for a significant proportion of breast cancer in Algerian young women.